The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fpsyt.2021.680393
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic Stress Symptoms in Adolescents Exposed to the Earthquake in Lombok, Indonesia: Prevalence and Association With Maladaptive Trauma-Related Cognition and Resilience

Abstract: Background: Natural disasters may physically and psychologically affect individuals and their surrounding community. This study determines the prevalence of post-traumatic stress (PTS) symptoms and its association with maladaptive trauma-related cognition and resilience among adolescents post-earthquake.Materials and Methods: Data were collected, in this cross-sectional study, during an intervention program post-earthquake held in a state high school located at Lombok, Indonesia. The study sample engaged stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…The high level of stress in adolescents affected by disasters depends on the time span between the event of the disaster and the time of evaluation, the region and quality of life, the severity of the disaster experienced, the level of education, the loss of immediate family or friends, the social support received and the perception of the acceptance of such social support [13] The results showed that adolescent girls have more depression than adolescent boys. These results are corroborated by other studies [14] which show that women are more vulnerable to developing symptoms of post-disaster stress due to high fear of threats.…”
Section: Findings and Discussionsupporting
confidence: 87%
“…The high level of stress in adolescents affected by disasters depends on the time span between the event of the disaster and the time of evaluation, the region and quality of life, the severity of the disaster experienced, the level of education, the loss of immediate family or friends, the social support received and the perception of the acceptance of such social support [13] The results showed that adolescent girls have more depression than adolescent boys. These results are corroborated by other studies [14] which show that women are more vulnerable to developing symptoms of post-disaster stress due to high fear of threats.…”
Section: Findings and Discussionsupporting
confidence: 87%
“…Similarly, PTSD, one of the stress-related disorders, was described as the most common psychological disease after a disaster. 86,87 Murray 79 addressed displaced refugees’ children who could be affected by PTSD due to an extended length of nightmares, sorrowful reactions, negligence, social withdrawal, psychological stress, and interrupted sleep. A considerable rise in stress levels was identified in IDPs living in temporary housing following the complex disaster resulting from the earthquake and tsunami that led to the Fukushima Daiichi Nuclear Power Plant accident (FDNPP accident); these levels are positively correlated to the length of time living in temporary housing.…”
Section: Discussionmentioning
confidence: 99%
“…Children might develop negative beliefs about themselves, including a negative self-view [46]. Traumatic experiences might also contribute to a negative worldview [4,[46][47][48]. Addressing post-traumatic cognitions is fundamental in helping children recover from the impact of traumatic experiences, and TF-CBT intends to identify maladaptive cognitions and help children develop more adaptive thought patterns and coping mechanisms [10,[48][49][50][51][52][53].…”
Section: Post-traumatic Cognitionsmentioning
confidence: 99%
“…Traumatic experiences like abuse, natural disasters, or loss of loved ones, may result in numerous harmful consequences on mental health [1][2][3][4], 2.6 times increasing the risk of depressive disorders [5], not to mention post-traumatic stress disorder (PTSD) [6,7].…”
Section: Introductionmentioning
confidence: 99%